Physical training for McArdle disease. - Quinlivan, R; Vissing, J; Hilton-Jones, D; Buckley, J (2011)
McArdle disease is a rare metabolic myopathy caused by a complete absence of the enzyme muscle glycogen phosphorylase. Affected people experience symptoms of fatigue and cramping within minutes of exercise and are at risk for acute muscle injury (rhabdomyolysis) and acute renal failure. If the first few minutes of exercise are paced, a 'second wind' will occur enabling exercise to continue. This is due to mobilisation and utilisation of alternative fuel substrates. Aerobic training appears to improve work capacity by increasing cardiovascular fitness. To assess the effects of aerobic training in people with McArdle disease. We searched the Cochrane Neuromuscular Disease Group Specialized Register (11 January 2011), CENTRAL (2010, Issue 4), MEDLINE (January 1966 to January 2011) and EMBASE (January 1980 to January 2011). All randomised and quasi-randomised controlled studies of aerobic exercise training in people of all ages with McArdle disease. Two authors identified possible studies for inclusion and assessed their methodological quality. Had more than one study of sufficient methodological quality been identified we would have undertaken a meta-analysis. There were no randomised or quasi-randomised controlled trials of aerobic training in people with McArdle disease. However, three open studies using small numbers of participants provided some evidence that aerobic training improves fitness without adverse events in people with McArdle disease. Evidence from non-randomised studies using small numbers of patients suggest that it would be safe and worthwhile for larger controlled trials of aerobic training to be undertaken in people with McArdle disease.